(untitled) - Lipkins, Susan (San Francisco, 2006)
Preventing Hazing uncovers the deep roots of hazing, how and why it permeates schools, colleges, and communities, and what parents, teachers, and coaches can do to prevent it. The author shows how to recognize the warning signs, what to do if a student has been involved in a hazing (either as a victim, bystander, or perpetrator), how to deal with the moral, legal, and emotional aspects of hazing, and, ultimately, how to heal and move forward both as an individual and a community.
Keywords: Bullying in schools,Hazing,Bắt nạt trong trường học,Bắt nạt; Prevention,Prevention,Phòng chống,Phòng chống